Preparation of the Czech Republic for the Regional Politics of the European Union - Regional Aspects versus Centralisation (Czech Journal of International Relations, 2002)
The relationship between Europeanisation and regionalisation is the subject of considerable debate. Some scholars claim that European Union (EU) regional policy has been a major factor in the shift of political authority and activity from the national to the regional level of governance in Europe. EU policies, they argue, have promoted governmental decentralisation and strengthened regional actors vis-ŕ-vis national governments, thereby contributing to the emergence of a "Europe of the Regions". Others are sceptical of these claims. They argue that the impact of EU regional policy varies considerably from country to country, in accordance with such factors as member state size, governmental traditions, and existing territorial and constitutional arrangements. They also point to the ability of national governments to act as "gatekeepers," thus limiting the impact of EU policies on domestic politics. The debate about Europeanisation and regionalisation has largely focused on the current member states of the EU. Relatively little attention, by contrast, has been given to the regionalisation effects of EU policies in the candidate states for EU membership. This is an interesting question to investigate for several reasons, however. Several factors would appear to give the EU huge potential influence over the regionalisation of governance structures and the development of centre-region relations in the CEECs, even before accession. Has this in fact been realised? What has been the influence of the EU on the territorial politics and governance structures of the candidate states in the pre-accession period? Has adoption of the administrative and institutional requirements of EU regional policy actually promoted governmental decentralisation and empowered regional actors in these countries? Admittedly, the full e!ects of Europeanisation in the CEECs are difficult to assess at this point in time, before formal accession, but what are the implications of EU membership for the future of regionalisation and decentralisation in the candidate states? These are the key questions that this paper addresses in a case study of the Czech Republic. It argues that the regionalisation e!ects of the accession process have thus far been limited, and that the EU's influence in this regard has been highly ambivalent. On the one hand, EU influence has promoted the development of new structures for regional governance and administration in the Czech Republic. On the other, the technocratic nature of the accession process, and the Commission's demands for efficiency and expediency in accession preparations and the implementation of EU programmes, have had a contrary e!ect, reinforcing the centralist position of national authorities and undermining the Commission's nominal support for decentralisation and partnership.